Use of physiological biomarkers in diagnosis along with field trials of different trypanisidal drugs in camels of Cholistan desert. (July 2017) - Durrani, Aneela Zameer; Bashir, Zubair; Mehmood, Khalid; Avais, Muhammad; Akbar, Haroon; Ahmad, Waqas; Azeem, Muhammad
Abstract: The point prevalence of trypanosomiasis with different physiological biomarkers along with evaluation of the most responsive trypanosidal drug against trypanosomiasis under field conditions was studied. For this purpose a total of 300 free range camels were selected at different grazing and watering point in Cholistan desert. The study population of camels included 150 clinically suspected camels for trypanosomiasis and 150 healthy camels with normal temperature, pulse and respiration. For therapeutic trials 36 positively diagnosed animals were randomly divided into three experimental groups for therapeutic trials. Group A was treated with Imidocarb dipropionate (ID) @ 1.2 mg kg −1 body weight; Group B was treated with Diaminazine aceturate (DA) @ 3.5 mg kg −1 body weight and Group C was treated with Isometamidium chloride hypochloride (IC) @ 0.75 mg kg −1 body weight of camels. Data on risk factors of age, sex, ectoparasites, housing was also collected. Results revealed an overall 15% point prevalence of trypanosomiasis. There was significant (P < 0.05) decline in the values of physiological biomarkers of total erythrocyte counts, hemoglobin concentration, packed cell volume, serum total proteins and albumin while erythrocyte sedimentation rate was increased in infected camels as compared to healthy ones. Different hepatic enzymes including aspartate aminotransferase, alanine aminotransferase, gamma glutamyltransferase and alkaline phosphatase were also significantly increased in the infected animals. Therapeutic trials indicated that Isometamidium chloride hypochloride (IC) was more effective than Imidocarb dipropionate (ID) and Diaminazine aceturate (DA). It is concluded that haemato-biochemical parameters were important physiological biomarkers and IC was the most responsive therapeutic agent against trypanosomiasis in camels in field conditions. The risk factors analysis showed older camels (>5 years) showed highest infection while infection was found to be lowest in less than 1 year age group.